Efficacy of long-term sublingual immunotherapy as an adjunct to pharmacotherapy in house dust mite-allergic children with asthma - (:unkn) unknown (BLACKWELL PUBLISHING, 2007)
Although sublingual immunotherapy (SLIT) is accepted to be a viable alternative of specific-allergen immunotherapy, the efficacy of long-term SLIT in asthmatic children is not well established. The efficacy of 3 yr of SLIT in addition to pharmacotherapy was compared with pharmaco-therapy alone in a prospective, open, parallel-group, controlled study. Children with asthma aged 4-16 yr, sensitive to house dust mite (HDM) were followed up for a run-in period of I yr and then grouped as those who would receive SLIT + pharmacotherapy (n = 62) or pharmacotherapy alone (n = 28). All patients were evaluated based on symptom-medication scores and lung function tests every 3 months, as well as skin-prick test and serum total immunoglobulin E (IgE) levels annually for 3 yr. Children in the SLIT + pharmacotherapy group demonstrated significantly lower mean daily dose and annual duration of inhaled corticosteroid (ICS) usage when compared with controls. At the end of the 3 yr, within-group comparisons revealed statistically significant decreases in the dose and duration of ICS only in the SLIT group. Furthermore, 52.4% of subjects in the SLIT + pharmacotherapy group were able to discontinue ICS treatment for at least 6 months, which was only 9.1% for the pharmacotherapy group. Three years of SLIT as an adjunct to pharmacotherapy resulted in reduction of both the duration and dose of ICSs and successful discontinuation of ICSs along with improvement in lung functions in HDM-allergic children with asthma.
Keywords: house dust miter; inhaled corticosteroids; paediatric asthma; sublingual immunotherapy; PLACEBO-CONTROLLED TRIAL; DOUBLE-BLIND; CLINICAL-EFFICACY; IMMUNOLOGICAL MECHANISMS; SWALLOW IMMUNOTHERAPY; POLLEN EXTRACT; RHINITIS; RHINOCONJUNCTIVITIS; INFLAMMATION